Using a Novel Neutrosophic Set-Based Method to Evaluate the Design Risk of Aerospace Manufacturing Projects in a Neutrosophic Environment - Hsiang-Yu Chung; Kuei-Hu Chang (International Journal of Computational Intelligence Systems)
Abstract During product design and manufacturing stages, unexpected challenges often occur, leading to product development or production failures. These failures can adversely affect the manufacturer's production efficiency, profitability, and reputation. Therefore, the industry often uses the failure mode and effects analysis (FMEA) approach to assess risk and identify possible risk factors. Moreover, with the rapid advancement of science and technology, shortened product life cycle, and the need for diversified product functions, factors such as time constraints, increased product manufacturing complexity, and difficulties in handling cross-domain information have made risk assessment in the design and manufacturing stages increasingly complex and challenging. These complexities can be considered a complicated multi-criteria decision-making (MCDM) problem. Due to the nature of the data, qualitative and quantitative data may coexist. On the other hand, decision-makers often lack a comprehensive understanding of cross-field expertise and information, leading to incomplete and inaccurate fuzzy information judgments. This, in turn, hinders their ability to provide accurate assessments of decision-making parameters in risk assessment issues. To address these challenges, this study integrates the FMEA method, the analytic hierarchy process (AHP) method, and the neutrosophic set (NS). It then applies these methodologies to numerical examples from an aerospace electronics manufacturing project for analysis and calculation. Compared with other research methods, the experiment results revealed that the novel NS-based risk analysis method yields more reliable and accurate rankings in failure mode risk in practical applications.